Preventing Malnutrition in Children Under Two Years of Age Approach - Ruel, Marie T. (International Food Policy Research Institute, 2010)
A study conducted by IFPRI in Haiti provided the first programmatic evidence, using a cluster randomized evaluation design, that preventing child undernutrition in children under two years of age (PM2A) through an integrated program providing food rations, BCC and preventive health and nutrition services is both feasible and highly effective. The study's principal aim was to compare a newly designed preventive approach with the traditional (recuperative) food assisted MCHN program approach, and therefore included only two comparison groups: one group of communities that was randomly assigned to the preventive approach and another group assigned to the recuperative approach. For logistical and financial reasons, the study did not include a randomized control group receiving no intervention.